LANGUAGE, POWER, AND IDENTITY: APPLIED LINGUISTICS IN MULTILINGUAL PUBLIC SPACES IN MEDAN - Alika Sandra Hasibuan; Diah Kusyani (Rahis Cendekia Indonesia, 2025)
This study examines the linguistic landscape of Medan, Indonesia, focusing on how language is used in public spaces to convey power, identity, and social positioning. By analyzing ten different public signs across the city, the research highlights the role of language in shaping communication strategies in a multilingual urban environment. The findings show that English is predominantly used in commercial and professional contexts to signal global prestige and modernity, while Bahasa Indonesia remains the primary language for local communication, governance, and regulatory functions. Additionally, the presence of regional languages such as Mandarin reflects cultural and ethnic identities within the community. This paper illustrates how the strategic use of language in public signage not only informs but also constructs social hierarchies, cultural identities, and power dynamics. Through an applied linguistic lens, the study contributes to understanding how public language use functions as a site of negotiation between local, national, and global forces.